A promising approach to wound healing – in-vivo study of carbon nanodots infused PVA hydrogel with Kamias extract as antibacterial wound dressing - Hipolito, Marilene C. (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The use of carbon nanodots (C-nanodots) synthesized from Kamias leaves for developing antibacterial wound dressings has gained attention due to their potential in promoting wound healing and contraction. To extract Kamias leaves, synthesize C-nanodots through microwave-assisted pyrolysis, characterize the synthesized C-nanodots, and test the polyvinyl alcohol (PVA) hydrogel infused with C-nanodots for antibacterial activity and wound contraction in Sprague Dawley rats. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Kamias leaves extract was used to synthesize C-nanodots with varying amounts of monoethanolamine. The C-nanodots were characterized using UV-Vis spectrophotometer, electron microscope, and the paper disk method. The PVA hydrogel infused with C-nanodots was tested for antibacterial activity and wound contraction in Sprague Dawley rats. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The synthesized C-nanodots exhibited antibacterial properties against Staphylococcus aureus and Subtilis bacillus, with a zone of inhibition ranging from 15 mm to 23.6 mm at different concentrations. The carbon nanodots-PVA hydrogel patch showed potential wound healing ability, with significant differences in wound contraction compared to the positive and negative controls. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. C-nanodots synthesized from Kamias extract have potential applications in antibacterial and wound healing fields. However, further studies are required to investigate the mechanism of action and potential side effects of using carbon nanodots in these applications.